MORPHOMETRY OF THE HYDROGRAPHIC BASINS INSERTED IN THE URBAN AREA OF DOURADOS – MS – BRAZIL - Lima dos Santos, Leonardo; de Oliveira Ribeiro, Vinícius; Oliveira Diodato, Jonailce (UFPR, 2019)
The morphometric characterization of watersheds has great importance and appliance for the prediction of phenomena such as floods. The objective of this study was to delimitate and characterize morphometrically the hydrographic basins that encompass the urban area of the Municipality of Dourados / MS – Brazil, which derived from estimated physical variables obtained by applying a license-free GIS software. Based on a Digital Elevation Model (DEM), the following microcatchment characteristics were determined: area, perimeter, slope, altitude, and watercourse orders. Four morphometric parameters that express a direct or inverse relationship with the water quantity factors of a hydrographic source were calculated and analyzed, being them: compactness coefficient, shape factor, circularity index, and drainage density. By comparing the studied basin results, it was observed that Água Limpa, Água Boa, and Laranja Azeda basin streams are more susceptible to flooding, especially considering the measurement factor and drainage density.